Nutritional Composition of Gluten-Free Labelled Foods in the Slovenian Food Supply - Lavriša, Živa (Int J Environ Res Public Health, 2020)
The market of gluten-free (GF) foods has been expanding in recent years. GF foods are consumed not only by those with medical predispositions for avoiding gluten, but also by a specific segment of consumers, searching for “healthier” food choices. For these, such practices can present a serious limitation in the variability of food choices. Considering that GF foods are commonly perceived as healthier alternatives, there is a lack of knowledge on the nutritional profile and content of specific nutrients of GF-labelled foods compared to general food supply. A comparison of nutritional composition of GF/non-GF packed foods in the Slovenian food supply was conducted. The nutrient profiling scoring criterion (NPSC) and content of specific nutrients/energy was compared between GF-labelled and regular foods. The highest proportion of GF-labelled products were found in food categories, which typically do not contain gluten (Cheese imitates, Milk imitates, Yoghurt imitates, Canned fish and seafood and Processed meat). Significant differences in the nutrient profile between GF-labelled and regular products were found in Cakes, muffins and pastry, Crisps and snacks, Desserts and Milk imitates. GF-labelled foods often had lower protein and sugar content. Energy value was comparable in most categories and no significant differences in salt content were found, compared to non-GF products. In conclusion, GF-labelled foods will unlikely bring health benefits to those who are not medically required to follow GF diet. Public health initiatives should aim towards promotion of consuming non-processed foods and provision of reliable information about who is required to consume GF foods.